INTERGRASI PASAR BERAS VERTIKAL ANTARA PETANI DAN PEDAGANG GROSIR DI INDONESIA - Muhlis, Muhlis; Nababan, Benny Osta (Jurnal AGRISEP, 2021)
This study aims to examine the vertical rice market integration between the rice market at the farmer level and the rice market at the wholesale trader level. This research uses monthly rice price for farmers and wholesaler from January 2013-July 2020 obtained from the Central Bureau of Statistic Indonesia. The results of the cointegration test indicate a long-term balance relationship between price changes at the farm level and prices at the wholesaler level. The estimation results of the vector error correction model show that the short-term balance relationship only occurs between changes in wholesale prices affected by changes in wholesale rice prices three months ago, premium rice prices at the farmer level three months ago and medium rice prices at the farmer level one month ago. The change in rice prices at the farmer level was only the premium rice price which was influenced by changes in the price of rice at the wholesale level three months ago.